Explorasi Gaya Bahasa Perulangan dalam Novel “BedeBah di Ujung Tanduk” Karya Tere Liye - Faulia, Mayza; Rahayu, Sri (UIR Press, 2024)
This research is motivated by the repetition style of language, which can be understood as a form of repetition that has five aspects namely figures of repetition, parallelism, anafora, polysyndeton, and asyndeton. The problem in the research is how the repetition style of language contained in the novel Bedebah di Ujung Tanduk by Tere Liye. The purpose of the research is to describe, analyze, and interpret the repetition style of language in the novel Bedebah di Ujung Tanduk by Tere Liye. The theory used is the theory of Burhan Nurgiyantoro (2014) and several other supporting theories. The research method is descriptive method. The approach used in the research is a qualitative approach. The results of the research are the presence of repetition style of language including figures of repetition which means simply repeating certain forms for example forget defense, forget evasion, dodge, they really fight openly, parallelism means there are several consecutive sentences that use the same structural pattern for example we will not let Ayako-san's sacrifice be in vain. We will not win against the Drukpa Spirit, anafora means the form of repetition is at the beginning of the syntactic structure with examples of missing each other but not calling each other. Like each other but not willing to talk, polysyndeton means the use of certain duty words marked by the word